TRANSFORMATION TO SOME GROWTH MODELS WIDELY USED IN AGRICULTURE - M. Korkmaz; F. Uckardes (Journal of Animal and Plant Sciences, 2013)
A mathematical model is a tool used to obtain information about the behavior of a system. The mathematical models can be used to have a preliminary knowledge about the functioning of a system, reducing the product costs and improving the performance. The aim of this study is related to how some of the sigmoidal models widely used in agriculture are converted to mechanistic models which have biological meaning. For this purpose, the commonly used six different models with sigmoidal structure were used. These models are Gompertz, Janoschek, Richards, Stannard, Weibull and Vonbertalanffy models, respectively. The three parameters “maximum specific growth rate (max), reached maximumvalue (A) and lag time (λ)” which are important in defining the growth, are shown, step by step, how to integrate into the models. As a result of this, these three biologically meaningful parameters have been gained in the models. In addition, we have also given on time of the inflection point and time of the inflection value of these models.
Keywords: Emprical model; Mechanistic model; Sigmoidal curve; Growth models; Lag time; Maximum specific growth rate; Reached maximum value